2011
DOI: 10.1016/j.exer.2010.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Genistein and genistein-containing dietary supplements accelerate the early stages of cataractogenesis in the male ICR/f rat

Abstract: Cataract-related loss of vision affects large numbers of people in today’s aging populations and presents a healthcare burden to many nations. The role of dietary supplements within the lens is largely unknown, although benefits from dietary antioxidants are expected. In this study, the effects of genistein as its aglycone, a genistein-containing dietary supplement (Novasoy®200), and a genistein-containing food (soy protein isolate, PRO-FAM 932) on the development of lens opacity were examined in the hereditar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…A result inconsistent with other studies was reported by Floyd et al [ 80 ]. In this study, rats were fed ad libitum different diets containing genistein at a concentration of 0.018% in different forms: as an aglycone or β-glucoside (derived from Novasoy ® 200 and PRO-FAM 932 Soy Protein Isolate (SPI)), and also at a concentration of 0.2% as an aglycon.…”
Section: Genistein As a Biologically Active Plant Compoundcontrasting
confidence: 98%
“…A result inconsistent with other studies was reported by Floyd et al [ 80 ]. In this study, rats were fed ad libitum different diets containing genistein at a concentration of 0.018% in different forms: as an aglycone or β-glucoside (derived from Novasoy ® 200 and PRO-FAM 932 Soy Protein Isolate (SPI)), and also at a concentration of 0.2% as an aglycon.…”
Section: Genistein As a Biologically Active Plant Compoundcontrasting
confidence: 98%
“…Genistein (GNT), a phytoestrogen that belongs to the family of isoflavones, is ingested as a component of vegetables (e.g. soy beans, fava beans, lupins) or as a dietary supplement [ 27 , 28 ]. GNT is considered to exert antioxidant and anticarcinogenic effects [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, genistein can be found as a dietary supplement consumed by women mainly in the developed world. Soy-derived isoflavone supplements which contain high amount of genistein include a concentrated extract of soy isoflavones (Novasoy ® 200) 3 and a low fat protein product such as PRO-FAM 932 soy protein isolate (SPI) 4. High genistein consumption has been proposed to adversely affect the reproductive functions in female based on the reported high incidence of infertility in sheeps fed with a specific species of clover, ' Trifolium subterraneum', known to contain high amount of isoflavone content 5.…”
Section: Introductionmentioning
confidence: 99%